1994
DOI: 10.1177/011542659400900265
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cyclic Parenteral Nutrition in Infants Less Than 6 Months of Age

Abstract: Cyclic parenteral nutrition is the technique of infusing the intravenous solution in less than 24 hours, during a portion of the day or night, allowing the patient freedom from the intravenous tubing and pump apparatus. In addition, adverse effects of long-term parenteral therapy, such as liver complications, were reported to be decreased with the use of cyclic parenteral nutrition in adult patients. Literature on the method and effects of cycling in young infants is minimal. This report describes cyclic paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 5 publications
1
20
0
Order By: Relevance
“…Cycling is achieved by gradually increasing rate over shorter infusion time. In small infants without enteral feeds, cycling off may be limited to 6 hours 50 . In a retrospective review of neonates with gastroschisis, cholestasis at 50 days was observed in 9.8% of the cycled group versus 48.8% in the group 51 receiving continuous PN.…”
Section: Cyclingmentioning
confidence: 99%
“…Cycling is achieved by gradually increasing rate over shorter infusion time. In small infants without enteral feeds, cycling off may be limited to 6 hours 50 . In a retrospective review of neonates with gastroschisis, cholestasis at 50 days was observed in 9.8% of the cycled group versus 48.8% in the group 51 receiving continuous PN.…”
Section: Cyclingmentioning
confidence: 99%
“…In other studies, it has been associated with improved serum bilirubin levels in adult patients compared with traditional continuous PN [25,26]. The use of cyclic PN in neonates as a means to normalize hyperbilirubinemia was first described in 1979, but subsequent reports in the neonatal population have been limited to descriptive studies [27][28][29]. Cyclic PN in adults is usually performed in 12-hour intervals, but this is not generally possible in the neonatal population due to diminished glycemic reserves, limiting safe cycling to much shorter time intervals of up to 6 hours [28].…”
mentioning
confidence: 99%
“…‐ 44 In the event that hyperglycemia does occur in the setting of high dose intravenous fat emulsion provision, lowering the fat emulsion dose should be considered due to its role in gluconeogenesis. In patients receiving cycled PN, intravenous dextrose and PN formulations should be tapered off over 1‐2 hours to prevent reactive hypoglycemia 45 , 46 …”
Section: Methodsmentioning
confidence: 99%